Estimation and Prediction of Case Fatality Rates, Recovery-to-Death Ratio of COVID-19 Disease during the Second Wave in Bangladesh - Muyeed, Abdul; Siddiqi, Md. Nure Alam; Islam, Md. Reazul; Shadhana, Supti Chakrabarty (Journal of Health & Biological Sciences, 2021)
Objectives: This study aimed to estimate the CFR and RDR of COVID-19 disease during the second wave in Bangladesh and also intended to predict the trend of COVID-19 infected and death cases, case fatality rate (CFR) and recovery-to-death ratio (RDR) using Facebook Prophet Model (FPM). Methods: Daily time series data of COVID-19 cases for 512 days used in this study was taken from worldometer. The FPM was used to predict the daily infections, deaths, CFR, and RDR of COVID-19 disease in Bangladesh as of August 01, 2021. Results: About 71% male and 29% female people were infected, most susceptible age group to be infected was 21 to 30 (27.6%) and below 10 (2.9%) was the least infected group as of August 01, 2021. The oldest age group (>60) was the most endanger to death (55.2%) and the youngest (<10) was the least death (0.3%) age group. Overall CFR was found at 1.654% which is less than the world CFR (2.13%) on August 01, 2021. The RDR was estimated at 52.269 which is below the world RDR 42.36 on August 01, 2021, in Bangladesh. Predicted infections and deaths exhibited an upward trend, daily CFR designates roughly constant trend, and daily RDR indicates a downward trend in Bangladesh at this ongoing second wave. Conclusion: The male people are more prone to be infected and dead. The oldest age group is more threatened to death and the youngest is least due to COVID-19 in Bangladesh. Both the predicted infections and deaths increasing, daily CFRs are roughly constant and daily RDR is decreasing in the second wave in Bangladesh due to the COVID-19 pandemic.